A Strategy for Teaching Interior Design through Reality-Based Project: An Experiential Study - Abdallah, Karam (الجمعية العلمية للمصممين, 2022)
The interior design studio is an important process, which aims to shape the design sensitivities of students and develop their communicative abilities as well as their problem-solving skills. Within this context, the research studies a strategy for teaching interior design through a reality-based project. It is based on the analysis and evaluation of a practical experience that was applied to the third-level students at MSA university, faculty of Arts & Design, department of interior design – design studio III (Commercial Design) unit – the academic year 2020/2021. Where a group of students designed a real project for a real client. The research aims to peruse the extent of benefits from applying the reality-based project as one of the teaching strategies and find the best way to apply this strategy. The research explains this strategy and its importance from the point of view of modern learning theories. It outlines the most important related studies that have applied this strategy in the academic field. This concludes the preferred applications that should be followed in these types of strategies and found learning outcomes and criteria upon which students' projects are evaluated. Then it will discuss the applied experience, and concludes the results and recommendations by analyzing the final projects based on the criteria concluded from the previous studies, and through a questionnaire answered by the students. Problem: Does teaching interior design through a reality-based project achieves the learning outcomes and the interior design process better than the virtual project? Objectives: The research aims to deduce the benefits of applying the reality-based project as a teaching strategy in teaching interior design studios. Methodology: The research adopts experiential and analytical methods. It introduces the opinions of specialized scholars and academics on the importance of the reality-based project strategy and its relation to the experiential learning approach. The related study helps to conclude a set of learning outcomes provided by the reality-based project. Then the research analyzes the practical experience carried out by the students and evaluates it in light of 1) the learning outcomes of the unit, 2) the learning outcomes provided by the reality-based project, which was deduced from previous studies, 3) a questionnaire that surveys the students’ opinion to measure the extent to which they benefited from applying the reality-based project strategy.
Keywords: التصميم الداخلي -- استراتيجيات التدريس -- طلبة الجامعات -- التعلم التجريبي